Estimating the Amount of Methane Gas Generated from the Solid Waste using the Land GEM Software, Sistan and Baluchistan - Mohammad Reza Narooie (Journal of Global Pharma Technology, 2017)
The biodegradation of organic compounds in the waste produces different gases such as methane gas. Despite the adverse greenhouse effects of the methane, this gas has many fuel values. Since estimating the amount of methane gas produced from the waste can be an economic and useful way for more accurate control and management of waste disposal in the Sistan and Baluchistan Province, conducting this study is essential. In this research, after collecting required information such as population, growth rate, the results obtained from the physical and chemical analysis of the waste, geographic data and the desired disposal system using LandGEM software, the methane generation potential obtained from the waste disposal in the Sistan and Baluchistan Province was investigated. The results of this study showed that the methane production potential in the Sistan and Baluchistan Province is 147 m3/ton, and if the waste disposal process was started in 2006, the methane generation would be 567 m3/h in 2011 and by considering a 20-years period, this amount will be 3596 m3/h in 2026. Therefore, according to the presence of adequate landfill sites in the Sistan and Baluchistan Province, it can be concluded that the controlled burial along with the gas extraction equipment in this province is a useful way for the waste management.Keywords: Estimating, LandGEM, Methane, Solid Waste, Sistan and Baluchistan